IMPROVEMENT OF THE MECHANISMS OF ENSURING THE EMPLOYMENT OF GRADUATES OF HIGHER EDUCATIONAL INSTITUTIONS ON THE BASIS OF DIGITAL TECHNOLOGIES (Scientific electronic journal "Labor Economics and Human Capital", 2025)
In the article, the problems of ensuring the employment of graduates of higher educational institutions were researched, as a conclusion of the research work, it was concluded that the mechanisms of ensuring the employment of graduates should go through the process of transformation on the basis of digital technologies.
Keywords: Digital technologies, higher education institutions, employment, digital economy, graduates.